Insight into The Status of Cardiothoracic and Vascular Surgery Training in Nepal - Tiwari, Kaushal Kishore (Journal of National Heart and Lung Society Nepal, 2024)
Cardiothoracic and Vascular Surgery is at a developing stage in Nepal. In Nepal, training of CTV surgeons started in the beginning of the 21st century. Nevertheless, there is already a decrease in trainee’s interest in this specialization leading CTVS training to a gasping state at its very neonatal age. Globally, training of medical professionals, in particular CTV surgeons, has been under continuous evolution since its inception. Analogously, in Nepal, the duration of the CTVS training and academic curriculum needs upgrading to meet international standards. Introduction of new concepts, learning advanced diagnostic and therapeutic techniques is important for CTV surgeons in Nepal, to become a competent member of the multidisciplinary Heart Team.